Connecting India Through Digital Media (Trinity Journal of Management, IT & Media (TJMITM), 2016)
Today Digitally empowered India is a scintillating dream of every  citizen. “The more technology we infuse in Governance, the  better it is for India” these are the words of our Hon’ble Prime  Minister who envisions transforming our nation and creating  opportunities for all citizens by harnessing digital technologies.  His vision is to empower every citizen with access to digital  services, knowledge and information. A well connected nation  is a rudiment to well served nation. Digital Technologies, which  include Cloud computing and Mobile Applications, have emerged  as catalysts for rapid economic growth and citizen empowerment  across the globe which will have its major impact on the urban  and rural areas. Even though many other countries have already  progressed in many areas of Digitalization and India has started  quite late but I am sure this is going to be worth it and this will be  utilized to its maximum potential. Information technology brings  a new opportunity-the digital opportunity for the rural population  of the country who often suffered by geographical, cultural and  linguistic barriers. This will provide them immense possibilities  to access information and services. Riding on digital networks  Indians are connecting and communicating with each other  through mobile phones and computers .This study shall discuss  how Digital India is going to revolutionize the way India connects,  examining 9 main pillars of Digital India, its projects, estimated  cost and impact, role of IOT (Internet of Things, usage of IT in  deliverance of services related to various domains such as health,  education, agriculture etc., Reducing paperwork with innovative  ideas, role of Bharat Broadband Network Limited (BBNL), Ratan  Tata’s views on Digital India, contribution by Facebook, Google,  Microsoft, Qualcomm and vision of Digital India that every  household, every individual should be digitally empowered.
Keywords: Digital; Empowerment; Cloud Computing; Pillars; Information Technology; Rural India; innovation; development; Modi Government; e-Governance; paperless